2017
DOI: 10.1515/cclm-2016-1002
|View full text |Cite
|
Sign up to set email alerts
|

Multidisciplinary training activities for decreasing preanalytical mistakes in samples from primary care

Abstract: Although the presence of PM remains slightly high, there was a significant reduction after the clinical update sessions in LAB1, where the most frequent PM was haemolysed sample. In contrast, the PM rates were slightly increased at LAB2, and the main source was missed sample. This might be explained, at least in part, by different problems associated with sample transportation, and by the delay in transferring acquired knowledge into clinical practice. Implementation of regular programme of update sessions and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
32
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(32 citation statements)
references
References 11 publications
0
32
0
Order By: Relevance
“…Low preinterventional HR (0.2%–10%) was observed in the studies conducted in Europe, n = 5 (Bolenius et al, ; Cadamuro et al, ; Romero et al, , ; Yazar et al, ), in comparison with Ong et al (), an Asian study (19.8%). However, Corkill (), an Australian study, reported no baseline rate.…”
Section: Resultsmentioning
confidence: 81%
See 4 more Smart Citations
“…Low preinterventional HR (0.2%–10%) was observed in the studies conducted in Europe, n = 5 (Bolenius et al, ; Cadamuro et al, ; Romero et al, , ; Yazar et al, ), in comparison with Ong et al (), an Asian study (19.8%). However, Corkill (), an Australian study, reported no baseline rate.…”
Section: Resultsmentioning
confidence: 81%
“…Three involved multiple pre‐analytical errors (i.e., rate of clotted and insufficient samples and impact on use of quality labels) besides haemolysis rate (Lillo et al, ). Similarly, Romero et al () and Romero et al () had multiple outcomes (i.e., missed sample, incorrect volume) and haemolysis rate. One study (Ong et al, ) was clear on the study limitation (Table ).…”
Section: Resultsmentioning
confidence: 92%
See 3 more Smart Citations